Caracterización geomorfológica de la cuenca del Río Tahuando y análisis sobre su capacidad de escurrimiento de aguas - Benavides Orbe, Elías Sebastián (2023)
The Tahuando River Basin runs along the eastern range of the northern “Sierra region” of Ecuador. It constitutes an area of socio-environmental influence as its waters flow through several rural and urban settlements within the province of Imbabura. In response to this issue, this study aims to characterize the geomorphology and understand the water runoff dynamics of the basin, as well as identify areas of threat or risk within it, using thematic maps generated through Geographic Information System (GIS) technology (ArcGIS 10.7.1). This study analyzed the shape, physical properties, and hydrological network of the watershed, the results of which provided insights into its geomorphological characteristics and the functioning of its drainage network, the final result indicates that water runoff within the basin occurs moderately, suggesting it is a basin in equilibrium or a mature phase, which implies a low erosive and sedimentary potential. Concerning the threat of risks, it was observed that the areas most susceptible to landslides are concentrated primarily in the upper basin, i.e., the mountainous area, while areas with a higher susceptibility to flooding are more widespread within the main channels of the hydrological network.